Synergistic effects of a novel free-standing reduced graphene oxide film and surface coating fibronectin on morphology, adhesion and proliferation of mesenchymal stem cells1. Issue 21 (7th June 2015) - Jin, Lin; Zeng, Zhiping; Kuddannaya, Shreyas; Yue, Dan; Bao, Jingnan; Wang, Zhenling; Zhang, Yilei
<x xml:space="preserve">Abstract</x> Fabrication of free-standing reduced graphene oxide (RGO) films by vacuum filtration of graphene oxide aqueous solution through a nanofiber membrane in combination with chemical reduction.